Kinerja Pengolahan Limbah Padat Serat Buah Sawit Menggunakan Metode Windrow Aerob Ditinjau Dari Rasio C/N - tania, Nindy; Ahmad, Adrianto; Andrio, David (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Solid waste produced by the palm oil processing industry consists of oil palm empty bunches (20-23%), fiber (10-12%), and shells (7-9%). Until now, the solid waste of palm fruit fiber is used as a potential energy source to be burned as boiler fuel. But along with the increase in Crude Palm Oil (CPO), there are still many palm fruit fibers that are not utilized optimally so that the waste only accumulates in the factory area, so the alternative sollution that can be done is by composting. Composting of palm fruit fiber waste with the addition of POME liquid waste which aims to determine the effect of adding Palm Oil Mill Effluent (POME) liquid waste with variations of 0%, 20%, 30% and 40% to the C/N ratio and measurements of C, N, pH, water content, and measurements are carried out. temperature, and the compost product is compared to compost quality standards (SNI 19-7030-2004). The results showed that the effect of POME addition at 20% gave the best results as indicated by the content of C/N 10.81, pH 6.99, water content 42.44% and temperature 32.06 oC, and compost product fulfill the quality standards SNI 19-7030-2004 compost. Thus, the best composting performance of palm fruit fiber waste is the addition of 20% POME with the fastest composting time at 25 days. Utilization of palm fruit fiber is one of the solutions to sustainable environmental pollution control. Key Words: Composting Process, C/N Ratio Palm Fruit Fiber, Palm Oil Mill Effluent (POME), Windrow.